High Variability in Radiologists' Reporting Practices for Incidental Thyroid Nodules Detected on CT and MRI - Hoang, J.K. (AJNR Am J Neuroradiol, 2014)
BACKGROUND AND PURPOSE: There are no guidelines for reporting incidental thyroid nodules seen on CT and MR imaging. We evaluated radiologists' current reporting practices for incidental thyroid nodules detected on these imaging modalities. MATERIALS AND METHODS: Radiologists were surveyed regarding their reporting practices by using 14 scenarios of incidental thyroid nodules differing in size, patient demographics, and clinical history. Scenarios were evaluated for the following: 1) radiologists' most commonly selected response, and 2) the proportion of radiologists selecting that response (degree of agreement). These measures were used to determine how the patient scenario and characteristics of the radiologists affected variability in practice. RESULTS: One hundred fifty-three radiologists participated. In 8/14 scenarios, the most common response was to “recommend sonography.” For the other scenarios, the most common response was to “report in only body of report.” The overall mean agreement for the 14 scenarios was 53%, and agreement ranged from 36% to 75%. Smaller nodules had lower agreement: 43%–51% for 8-mm nodules compared with 64%–75% for 15-mm nodules. Agreement was poorest for the 10-mm nodule in a 60-year-old woman (36%) and for scenarios with additional history of lung cancer (39%) and multiple nodules (36%). There was no significant difference in reporting practices and agreement when radiologists were categorized by years of practice, practice type, and subspecialty (P > .55). CONCLUSIONS: The reporting practice for incidental thyroid nodules on CT or MR imaging is highly variable among radiologists, especially for patients with smaller nodules (≤10 mm) and patients with multiple nodules and a history of cancer. This variability highlights the need for practice guidelines.